Multi-scale analysis of current-driven spin dynamics in magnetic tunnel junctions - GALANTE, MARIO (Trinity College Dublin. School of Physics. Discipline of Physics, 2020)
Magnetic materials are of fundamental importance for the next generation of sensing and storage applications. The operating principle of such devices is based upon manipulating the orientation of the atomic magnetic moments. The dynamics of the latter can be efficiently driven through the injection of spin-polarised currents that generate effective torques, by spin conservation. These are commonly known as spin torques. State-of-the-art devices employ two ferromagnets sandwiching an insulating spacer, i.e. a magnetic tunnel junction, where information is stored in the mutual orientation of the two magnetisations. These structures are engineered so that the magnetisation vector of one magnetic layer is kept fixed along a given direction, while the magnetisation of the other ferromagnet, also known as free layer, can be reversed with an electric current. The elevated sensitivity of the magnetisation switching to factors such as the properties of the ferromagnet, the quality of the interfaces and temperature fluctuations makes the search of novel materials for these applications a troublesome task. Here we present a multi-scale study of the magnetisation switching in Fe/MgO-based magnetic tunnel junctions for different compositions of the free magnetic layer. We begin by investigating the atom-dependence of the spin torques with the objective of determining the factors that define their materials dependence. This is done by the means of quantum transport calculations performed with a combination of non-equilibrium Green's functions and density functional theory. The calculated spin torques are then used as input for spin dynamics simulations at the atomistic scale, in order to compare the current-driven magnetisation switching in the different systems at different temperatures. We find that the general spatial profile of the spin torques for a given free layer can be predicted from the band structure of the ferromagnet. However, in many cases the presence of additional interfaces or non-uniform magnetic textures drastically modifies the predicted profile. Nevertheless, the details of the decay of the spin torques do not imply significant modifications of the switching properties. In fact, we find that the critical voltage required to obtain magnetisation reversal is essentially dictated by the total torque acting on the free layer. We continue with a study of antiferromagnetism in the Mn_3Ga and Fe_2MnGa Heusler compounds, in which magnetic properties are dominated by the moments at the Mn sites. Antiferromagnetic materials are of great interest for spintronic applications, since they may push the spin dynamics in the THz range, as opposed to the GHz range of the one in ferromagnets. Our results show that the spin model for Mn_3Ga displays an extremely high-frequency oscillation mode, which is found to be characteristic of this system. In contrast, we find that the induced moments at the Fe sites in Fe_2MnGa are extremely sensitive to the presence of interfaces and to the alignment of the neighbouring Mn atoms. This is observed through both spin dynamics simulations and first principles quantum transport calculations. Finally, we derive a novel parameter-free method for the estimation of the Gilbert damping from first principles simulations.
APPROVED
Keywords: quantum transport; density functional theory; atomistic spin dynamics; magnetic tunnel junctions; antiferromagnetic spintronics; Gilbert damping